Global rarity of intact coastal regions. Issue 4 (6th February 2022) - Williams, Brooke A.; Watson, James E.M.; Beyer, Hawthorne L.; Klein, Carissa J.; Montgomery, Jamie; Runting, Rebecca K.; Roberson, Leslie A.; Halpern, Benjamin S.; Grantham, Hedley S.; Kuempel, Caitlin D.; Frazier, Melanie; Venter, Oscar; et al.
Abstract: Management of the land–sea interface is essential for global conservation and sustainability objectives because coastal regions maintain natural processes that support biodiversity and the livelihood of billions of people. However, assessments of coastal regions have focused strictly on either the terrestrial or marine realm. Consequently, understanding of the overall state of Earth's coastal regions is poor. We integrated the terrestrial human footprint and marine cumulative human impact maps in a global assessment of the anthropogenic pressures affecting coastal regions. Of coastal regions globally, 15.5% had low anthropogenic pressure, mostly in Canada, Russia, and Greenland. Conversely, 47.9% of coastal regions were heavily affected by humanity, and in most countries (84.1%) >50% of their coastal regions were degraded. Nearly half (43.3%) of protected areas across coastal regions were exposed to high human pressures. To meet global sustainability objectives, all nations must undertake greater actions to preserve and restore the coastal regions within their borders. Abstract : Article impact statement : Humanity's impact on Earth's coastal regions is severe and widespread; global efforts are required to preserve the remaining intact regions. Abstract : costa, huella humana, impacto humano cumulativo, litoral, presión humana, restauración, tierras vírgenes Resumen: El manejo de la interfaz entre la tierra y el mar es esencial para los objetivos mundiales de conservación y sustentabilidad ya que las regiones costeras mantienen los procesos naturales que sostienen a la biodiversidad y al sustento de miles de millones de personas. Sin embargo, los análisis de las regiones costeras se han enfocado estrictamente en el ámbito marino o en el terrestre, pero no en ambos. Por consiguiente, el conocimiento del estado general de las regiones costeras del planeta es muy pobre. Integramos la huella terrestre humana y mapas marinos del impacto humano cumulativo en un análisis global de las presiones antropogénicas que afectan las áreas costeras. De las áreas costeras de todo el mundo, el 15.5% tuvieron una presión antropogénica reducida, principalmente en Canadá, Rusia y Groenlandia. En cambio, el 47.9% de las regiones costeras estuvieron fuertemente afectas por la humanidad, y en la mayoría de los países (84.1%) >50% de sus regiones litorales se encuentran degradadas. Casi la mitad (43.3%) de las áreas protegidas en las regiones costeras tienen un grado de exposición a fuertes presiones humanas. Para cumplir los objetivos mundiales de sustentabilidad, todos los países deben emprender mejores acciones para preservar y restaurar las regiones litorales dentro de sus fronteras.